PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA DI MI/SD DAN ALTERNATIF PEMECAHANNYA - Puspidalia, Yuentie Sova (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract: The ultimate goal of Indonesian teaching is to help learners able to integrate themselves into the society successfully. This aim is in line with the development of science and technology in the globalization era, in which the role of the Indonesian language as a mean of personal development is inevitably challenged by the rapid changes and the need of international languages. For this reason, it is worried that learners face any negative wash back of the existence of International language, in instance, the lost of their own identity. To this end, the role of Indonesian teaching is getting more and more obviously important. In reality, however, the Indonesian teaching is generally assumed as the easiest subject if it is compared with other subjects. As a result of this case, learners pretend not to learn Indonesian seriously. Ironically, many students get low grade although the Indonesian lesson is seen easily to learn. In fact, elementary school (SD/MI) is regarded as basis for the formation of the noble values of the nation. The study had identified several sources of problems in learning Indonesian both from the educators or learners. Besides, it was revealed that the result of learning was affected by some aspects, such as the goals, materials, methods, school facilities and infrastructure.